Educação em tempo de crise - Dias de Carvalho, Adalberto; Universidade do Porto / ISCET / ESEPF (2012)
The contemporary crisis, while generating poverty andunemployment, touches our existence: spreads insecurity,steals dignity, imposes suffering, and leads manypeople to live by surviving. But the crisis also brings aproblem of meaning by threatening the horizon thatguides us, the foundations that sustain us and hope thattranscends us. It threatens also by demanding other horizons,other foundations, other forms to decline hope.It intensifies when these alternatives are slow to appear.